IMPLEMENTATION OF COMMUNICATIVE AND COGNITIVE APPROACHES IN TEACHING A FOREIGN LANGUAGE FOR SPECIFIC PURPOSES USING A CROSSWORD PUZZLE AS A TYPE OF A DIDACTIC GAME: didactic game; foreign language; cognitive approach; communicative approach; crossword puzzle; professional orientation - Baranovska, Liliia; Zasluzhena, Alla (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2022)
The article focuses on the use of communicative and cognitive approaches to teaching a Foreign Language for Specific Purposes (FLSP). They are implemented through a crossword puzzle as a type of a didactic game. The purpose of the article is to substantiate the expediency of using communicative and cognitive approaches in teaching FLSP using a didactic game. The objectives of the scientific work are to identify theoretical and methodological aspects of using these methodological approaches to improve the teaching FLSP, to substantiate the pedagogical expediency of using crossword puzzles as varieties of a didactic game for high-quality mastery by students with the terminology of their future profession. Results. The organization of the educational process based on a communicative approach involves the focus of the student's training in the development of grammatical, lexical, phonetic and speech skills by performing exercises that have a communicative focus. The communicative approach contributes to the formation and development of communicative competence. The definition of "communicative competence" has been refined. The significance of the cognitive approach lies in the organization of active speech and thinking activities of students, as they are provided by language abilities as individual characteristics of a person, knowledge of linguistic and encyclopedic character, skills and needful motivation and communication environment. Discussion. The academic discipline "Foreign Language for Specific Purposes" is taught to students of non-language specialties. Conceptually and pedagogically expedient is its study by using communicative and cognitive approaches. They contribute both to the integration of the content of a linguistic training course with the content of professionally oriented disciplines and create favorable psychological and pedagogical conditions for deepening the psycholinguistic aspect of teaching the discipline. The use of crossword puzzles in classes in this discipline is teamwork in the form of a didactic game, which allow sits participants to demonstrate and develop the skills o audio, oral and written speech, to master elements of the heuristic method; it meets the realization of the need for the development of critical and creative thinking of students through the development of all types of communication activities. Methods. Theoretical methods have been used, in particular, general scientific: analysis, synthesis, comparison, generalization, specifying, which ensured the possibility of forming the initial provisions and distinguishing the main ideas and scientific approaches that form the theoretical basis for the study of the problem; specific: terminological analysis that allowed to determine the definitions of key concepts; cause-effect analysis, which contributed to the determination of the conditionality of the results of communicative activity by the influence of psychological characteristics of participants in its various types; structural and functional analysis is used to clarify the psycholinguistic features of the processes of preparation and doing of crossword puzzles; empirical methods: analysis of the content of the working curriculum in FLSP, Bloom's Taxonomy method. Conclusions. In modern conditions, the teaching of a foreign language should be oriented primarily to the subjects’ knowledge of the educational process of the deep mechanisms of the influence of language on the mental development of a specialist. Conceptually and pedagogically expedient is its study based on communicative and cognitive approaches that contribute to the integration of the content of a linguistic course with the content of professionally oriented disciplines. A didactic game using crossword puzzles contributes to the formation of communicative skills of students, update their general scientifical resource with vocabulary oriented to the profession